An analysis to explore divergence of HMW glutenin subunits in high-yield Indian wheat of different production environments - Mohan, Devinder; Gupta, Raj Kumar (Journal of Cereal Research, 2017)
Fifteen years grain quality data of 231 high yielding bread wheat genotypes evaluated in different production environments of India was examined to understand prevalence of high molecular weight glutenin subunits (HMWGS) in different production environments. Six agro-climatically diverse zones and two production conditions (timely-sown and late-sown) perzone represented diverse wheat growth environments prevailing in India. Difference in frequency level of different subunits has been explained in this review. Accurance of various subunits varied promptly in diffrenrent zones (Glu B1) and climates (Glu D1). Diffrence as per production condition was also noticed in same variants of Glu B1 locus. Parallelism between quality of bread and the glutenin subunits was observed under varying wheat growth environments. It was further demonstrated that overall product quality of a given production environment can be better explained by ratio between desirable and undesirable HMW glutenin subunits.Â Doi.org/ 10.25174/2249- 4065/2017/70589